Pembinaan Kesehatan Mental dan Penguatan Nilai-Nilai Keislaman Peserta Didik Melalui Program Bina Karakter Islam di SMP Fatma Kenanga Kota Bengkulu - Kesi Mayori; Mawardi Lubis; Khairiah Khairiah (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to elucidate the development of students mental health and the reinforcement of Islamic values through the Islamic character building (BIKALAM) program at SMP Fatma Kenanga Bengkulu. Employing a qualitative descriptive methodology, data were collected via observation, interviews, and documentation. The findings reveal that the planning phase for mental health development and the strengthening of Islamic values among students encompasses four stages: defining objectivies, formulating activities, leveraging resources, and maintaining consistent execution. The implemention phase comprises two primary components: Mental Health Development: this includes fostering peace of mind and heart (through tawakkal and patience), self-control and emotional regulation (via taqwa and ihsan), discipline and orderliness (through worship and prayer), as well as optimism and hope (via husnuzan and acceptance of divine decree). Reinforcement of Islamic values: this involves habituating religious behavior among students, modeling exemplary conduct by teachers, adopting an empathetic approach t0wards students, and fostering synergy among teachers and school elements. The evaluation of mental health development and the reinforcement of Islamic values is conducted through monitoring progress, measuring outcomes, and identifying obstacles to program success.